Switching regulator based on an adaptive DC-DC buck converter for a lithium-ion battery charging interface - Rahali, Ahmed; El Khadiri, Karim; Qjidaa, Hassan; Tahiri, Ahmed (Institute of Advanced Engineering and Science, 2024)
A switching regulator based on an adaptive DC-DC buck converter for a Li-ion battery charging interface is introduced in this paper with the aim of improving the efficiency of charging the Li-ion battery during the whole charging process. By using the battery voltage as feedback, an adaptive reference is generated. This reference is employed by the converter, which is in continuous conduction mode (CCM), to produce a wide adaptive output voltage that closely tracks the battery voltage, intended to serve as the power source for the multimode charging interface. The converter was implemented in a 180 nm complementary metal oxide semiconductor (CMOS) process and simulated using the Cadence Virtuoso tool. With an input voltage of 5 V and a switching frequency selected at 500 kHz, the simulation results show that the converter produces different charging currents for each battery charging mode, and an adaptive output voltage ranging from 2.8 V to 4.38 V, with the current ripple of 38 mA in CC mode and voltage ripple factor less than 1% in constant voltage (CV) mode. The average converter efficiency is 83.5%.